On The Sufficient Conditions Of The Localization Of The Fourier-laplace Series Of Distributions From Liouville Classes - Anvarjon A. Ahmedov; Abdumalik Rakhimov; Ahmad Fadly Nurullah Rasedee (IOP Publishing, 2024)
In this work we investigate the localization principle of the Fourier-Laplace series of the distribution. Here we prove the suffcient conditions of the localization of the Riesz means of the spectral expansions of the Laplace-Beltrami operator on the unit sphere.